O impacto do programa mais educação no processo de aprendizagem dos alunos que participam das oficinas de música: um estudo de caso na escola Pinto Marques, no município de Acará-Pará - CHAVES, Eliel Rabelo das (2021)
The present work has as its theme “The impact of the More Education Program on the learning process of students who participate in music workshops: a case study at Pinto Marques Municipal School, in the municipality of Acará-Pará”, and aims to analyze the contributions of the music workshop of the More Education Program in improving students' learning at Pinto Marques Municipal School, Acará-Pará, reflecting important factors in the cognitive, motor and affective field, among others, stimulated by music in daily school life. The methodology used during the research appropriated the qualitative approach, in the form of case study, having as subsidies theorists such as Chizzotti (2006), Stake (1994), Gainza (1988), Brescia (2003), among others. The data collection technique used was the interview with semi-structured questions, conducted with the Program coordinator, art teacher, workshop monitor and a representation of students. The music workshops related to the More Education Program emphasize music as an important educational tool, in which the activities constitute a didactic-pedagogical resource, allowing the transversality between different knowledge and providing a greater interaction between the students in the learning process.